First farmers the origins of agricultural societies - Bellwood, Peter S. (Wiley Blackwell, 2023)
"The subject matter of this book falls mainly within the last 12,000 years of human migration history. It begins with the gradual retreat of Last Glacial Maximum (or last Ice Age) climatic conditions and extends through the warm Holocene conditions that the world enjoys now, conditions exacerbated by the human contribution known to most of us as "global warming". The book examines the development of food production through plant and animal domestication, and the repercussions of food production on human demography and migration. Even though food production can occur with species that are morphologically "wild" (i.e., not domesticated), the evolving systems of food production that have driven human migration history during the past 12,000 years have been based increasingly on domesticated species. The major hypothesis behind this book was described in the first edition as the early farming dispersal hypothesis. It drew in part from what Colin Renfrew (2002) had previously defined as the farming/language dispersal hypothesis, with the title modified slightly to reflect the importance of humans as biological entities, as well as agents of farming and language dispersal. Indeed, Colin and I had been working independently on the theme since the early 1980s, I in the Austronesian world and Colin in its Indo-European counterpart (Renfrew 1987). The early farming dispersal hypothesis suggests that, as the world emerged from the last Ice Age, humans in many tropical and temperate regions began to change their way of life from hunting and gathering to the production of food from domesticated plants and animals. As this movement into food production intensified, some (but not all) populations of farmers grew rapidly in number, especially in certain favored regions such as the Middle East, China, the central Andes, and Mesoamerica. With greater numbers, pressures grew to occupy more land for crops and pasture, resulting in outward migration into new territories that initially would have been occupied by hunter-gatherer populations who lived at lower population densities than the early farmers. With these new food producing migrants travelled their languages, genes, and ways of life. These spreads of food production, genes and associated languages clearly occurred deep in the realms of prehistoric time, long before the rise of literate civilizations and empires. The early farming dispersal hypothesis today has both supporters and detractors who undertake research in a world of fast-flowing and often revolutionary scientific results from archaeology, linguistics, and evolutionary biology/genetics. Does the hypothesis still carry conviction, some forty years or more after its original formulation? Readers of this book can judge. My own conviction is that, without food production, the world as we know it could not exist, and neither would most people alive today, nor the largest of the world's language families. I have updated my perspectives on human migration history in many other books since the original 2005 publication of First Farmers. Its Wiley Blackwell successor, First Migrants: Ancient Migration in Global Perspective (Bellwood 2013), deals with migration through all periods of human prehistory. My edited book The Global Prehistory of Human Migration (Bellwood ed. 2015) presents perspectives by many archaeologists, linguists and geneticists that cover prehistoric migration in much of the world. My most recent Wiley Blackwell book, First Islanders: Prehistory and Human Migration in Island Southeast Asia (Bellwood 2017), updates my perspective on southern China and Southeast Asia, especially for the Austronesian linguistic and population dispersal from origins in southern China and Taiwan. My most recent book, The Five-Million-Year Odyssey: The Human Journey from Ape to Agriculture (Princeton University Press, Bellwood 2022), presents for a general reader my views on the whole of hominin and human migration history. Some acknowledgements are necessary. The following have kindly read short sections of text that deal with their fields of expertise: Harry Allen, Tim Denham, Dorian Fuller, Norman Hammond, Charles Higham, Hsiao-chun Hung, Nicolas Peterson, Philip Piper, Martine Robbeets, and Peter Sutton. The excellent original maps of Jenny Sheehan prepared in the College of Asia and the Pacific at ANU have been updated by me using Adobe Illustrator, with many new ones added. Wiley Blackwell have kindly assisted in providing resources for obtaining copyright permissions where required for this edition. The Australian National Library made available the books and journal articles upon which this book is based, and I must acknowledge my continuing emeritus professorial status in the School of Archaeology and Anthropology at ANU that gives me access to such essential resources"-- Provided by publisher.